Consumer behavior change at the base of the pyramid: Bridging the gap between for‐profit and social responsibility strategies. (9th April 2014) - Jones Christensen, Lisa; Siemsen, Enno; Balasubramanian, Sridhar
<x xml:space="preserve">Abstract</x> This longitudinal field experiment compares two different for‐profit market entry strategies with a philanthropic strategy in terms of how each influences consumer behavior in base‐of‐the‐pyramid communities. We analyze reactions to a water purification product offered at three price points (moderate discount, deep discount, and free) in rural Malawi. We find that those who paid the deeply discounted price remain more likely to re‐obtain and use the product than do those who paid the moderate price or who took it for free. Copyright © 2014 John Wiley & Sons, Ltd.